5‐Alpha reductase inhibitor related litigation: A legal database review. (30th December 2021) - Low, Patrick; Li, Kevin D.; Hakam, Nizar; Bell, Alexander; Abbasi, Behzad; Lui, Jason; Shaw, Nathan M.; Breyer, Benjamin N.
Abstract: Background: 5α‐reductase inhibitors are commonly prescribed medications with multiple side effects used in the treatment of male pattern hair loss and benign prostatic hyperplasia. These side effects including "post‐finasteride syndrome" may result in lawsuits. Objectives: To characterize lawsuits involving the adverse side effects of 5α‐reductase inhibitor to better understand drivers of litigation and outcomes. Methods: Legal cases were queried from Nexis Uni using the search terms "5‐alpha reductase inhibitor" as well as specific agents "finasteride, " "dutasteride" in combination with "malpractice, " "negligence, " "damage, " "loss, " "side effect, " and "complication." Secondary review was performed with publicly available data on "In Re: Propecia." Relevant cases were reviewed and pertinent characteristics were extracted and summarized using descriptive statistics. Results: Our search yielded 156 unique legal cases in the Nexis Uni database from April 2003 to May 2021. Only 18 of these cases met the inclusion criteria. Adverse events experienced by patients included medication side effects ( n = 12, 66.7%), delayed cancer diagnosis ( n = 3, 16.7%), and lack of symptom improvement ( n = 3, 16.7%). The identity of the plaintiffs were most commonly patients themselves ( n = 15, 83.3%). Defendants include pharmaceutical companies ( n = 6, 33.3%), a combination of parties ( n = 5, 27.8%), and physicians ( n = 5, 27.8%) alone. The allegations included sexual side effects such as erectile dysfunction ( n = 6, 33.3%) and decreased libido ( n = 4, 22.2%). These prescriptions were made for benign prostatic hyperplasia ( n = 9, 50%), male pattern hair loss ( n = 7, 38.9%), and feminizing hormone therapy ( n = 2, 11.1%). Several of these cases involved the same plaintiffs in related cases. No verdicts were against physicians. We noted a largely settled lawsuit involving more than 1000 plaintiffs with limited data on harms alleged and a 4.3 million settled amount. Of the total cases that resulted in a verdict, 9/18 were within the last 3 years. Discussion: The most common complications experienced by patients in our legal review were those involving sexual dysfunction with erectile dysfunction and decreased libido. The growing number of cases in the later years of our review suggests litigation may continue to increase in the coming future. Our review did not identify any individual cases that resulted in a monetary payout beyond a 4.3 million settlement outside of court. Conclusion: 5α‐reductase inhibitor was alleged to have sexual, mental, and physical side effects, resulting in legal litigation. Despite this, no judgment against a physician or pharmaceutical company was identified. We do note and discuss a large number of lawsuits settled out of court. Given the increase in the number of lawsuits resulting in verdicts over the last 3 years, we suspect that the frequency of litigation around 5α‐reductase inhibitors will continue for the foreseeable future.